PENGARUH MEDIA PEMBELAJARAN TERHADAP MOTIVASI BELAJAR SISWA DI SMKN 26 JAKARTA - Farhana; Aulia Seftianingsih (Almarhalah: Jurnal Pendidikan Islam, 2023)
The focus of this research is to examine the use of learning media which is limited to one of the educational-based game applications, namely Quizizz. This study aims to determine the effect of using quizizz on student learning motivation in Islamic Religious Education subjects and to analyze teacher strategies to increase student motivation in learning. This study used a quantitative approach with a descriptive correlational analysis method. Using a questionnaire instrument distributed to 41 samples from 491 total population of class X at SMKN 26 Jakarta. The questionnaire instrument consists of 20 positive and negative statements on the variables X and Y. This study shows the results that there is an influence by using Quizizz on student learning motivation, this evidence comes from the hypothesis test ro > rt with a result of ro ​​of 0.436, the result is greater than "rt" a significant level of 5% is 0.316 and a significant level of 1% is 0.408 and the coefficient of determination is 0.190 or 19%. Thus the results of this study indicate that learning media using quizizz have a moderate/sufficient correlation with student learning motivation in PAI subjects with a value of 0.436 or 43.6%.